Stakeholder perspectives on non-invasive brain stimulation - Moritz Julian Maier; Perianen Ramasawmy; Johannes Breuer; Anne Bansen; Antonio Oliviero; Georg Northoff; Andrea Antal (Scientific Reports)
Abstract Non-invasive brain stimulation (NIBS) techniques such as transcranial direct current stimulation (tDCS) or transcranial magnetic stimulation (TMS) have made great progress in recent years and offer boundless potential for the neuroscientific research and treatment of disorders. However, the possible use of NIBS devices for neuro-doping and neuroenhancement in healthy individuals and the military are poorly regulated. The great potentials and diverse applications can have an impact on the future development of the technology and society. This participatory study therefore aims to summarize the perspectives of different stakeholder groups with the help of qualitative workshops. Nine qualitative on-site and virtual workshops were conducted in the study with 91 individuals from seven stakeholder groups: patients, students, do-it-yourself home users of tDCS, clinical practitioners, industry representatives, philosophers, and policy experts. The co-creative and design-based workshops were tailored to each group to document the wishes, fears, and general comments of the participants. The outlooks from each group were collected in written form and summarized into different categories. The result is a comprehensive overview of the different aspects that need to be considered in the field of NIBS. For example, several groups expressed the wish for home-based tDCS under medical supervision as a potential therapeutic intervention and discussed the associated technical specifications. Other topics that were addressed were performance enhancement for certain professional groups, training requirements for practitioners, and questions of agency, among others. This qualitative participatory research highlights the potential of tDCS and repetitive TMS as alternative therapies to medication, with fewer adverse effects and home-based use for tDCS. The ethical and societal impact of the abuse of NIBS for non-clinical use must be considered for policy-making and regulation implementations. This study adds to the neuroethical debate on the responsible use and application of NIBS technologies, taking into consideration the different perspectives of important stakeholders in the field.